A PdMn bimetallene for low-energy electrocatalytic hydrogen generation coupled with formate oxidation. Issue 94 (8th November 2022) - Wang, Hongjing; Chen, Hongyong; Mao, Qiqi; Deng, Kai; Yu, Hongjie; Wang, Xin; Xu, You; Wang, Ziqiang; Wang, Liang
Abstract : A defect-rich and wrinkled PdMn bimetallene was fabricated via a one-step thermal solvent method for promoting formate electroreforming. Abstract : In this communication, a PdMn bimetallene is synthesized using a template-free solvothermal method with the assistance of diamines. The PdMn bimetallene with rich defects and highly curved structures shows superior performance for the formate oxidation reaction (FOR) and the hydrogen evolution reaction (HER). For the two-electrode HER–FOR system, the PdMn bimetallene achieves a much lower voltage of 0.376 V at 10 mA cm −2, demonstrating an energy-effective path for hydrogen production.